Acriflavine Uptake and Resistance in Serratia marcescens Cells and Spheroplasts - Woods, D. R. (1973)
Acriflavine uptake and resistance were investigated in red, sensitive Serratia marcescens cells and in orange, resistant mutant cells and their respective spheroplasts. Acriflavine-sensitive cells bound more acriflavine than acriflavine-resistant cells. Spheroplasts from sensitive and resistant cells were both resistant to and bound similar amounts of acriflavine. Sensitive cells were resistant to acriflavine in medium supplemented with 0.01 M MgSO(4) and 0.5 M sucrose. In the presence of 0.01 M MgSO(4) and 0.5 M sucrose, acriflavine binding by sensitive cells was reduced to the level of binding by resistant cells. Inhibition of metabolism by carbon starvation, chloramphenicol, As(2)O(3), nitrosoguanidine, and bromouracil did not affect the uptake of acriflavine by sensitive and resistant cells. Rapid temperature changes did not alter the acriflavine-binding capacity of the cells, and no temperature dependence of acriflavine uptake or release was observed at 0 and 30 C. Acriflavine uptake by both sensitive and resistant cells increased with increase in pH from 5.7 to 8.0. The logarithm of acriflavine uptake was a linear function of the logarithm of the acriflavine concentration in the binding medium.